The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1990
DOI: 10.1007/bf00178859
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interest rates, income, and employment upon regional housing prices

Abstract: The objective of this article is to identify important differences in the way new housing prices react to local and national economic factors. The study finds that regional housing prices react uniformly to certain national economic factors, such as mortgage rates. On the other hand, local factors such as population shifts, employment, and income trends often have a unique impact on housing prices. The study rejects the hypothesis of a single national housing market in favor of one that allows for broad nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 25 publications
2
90
1
1
Order By: Relevance
“…The correlation between interest rates, borrowing costs, and housing prices is well documented (Harris 1989;Reichert 1990;Poterba 1991;Englund and Ioannides 1997;Sutton 2002;and Tsatsaronis and Zhu 2004) 22 and, while its correlation with home sales has been much less discussed, there is a long tradition in economics that supports the predictive power of interest rate measures with respect to the evolution of the economy (Sims 1980;Stock and Watson 1989). For example, Bernanke (1990) shows how the interest rate measure we have used here, the Federal Funds Rate, is a good predictor of a large number of indicators of the real economy.…”
Section: Business Cyclementioning
confidence: 99%
“…The correlation between interest rates, borrowing costs, and housing prices is well documented (Harris 1989;Reichert 1990;Poterba 1991;Englund and Ioannides 1997;Sutton 2002;and Tsatsaronis and Zhu 2004) 22 and, while its correlation with home sales has been much less discussed, there is a long tradition in economics that supports the predictive power of interest rate measures with respect to the evolution of the economy (Sims 1980;Stock and Watson 1989). For example, Bernanke (1990) shows how the interest rate measure we have used here, the Federal Funds Rate, is a good predictor of a large number of indicators of the real economy.…”
Section: Business Cyclementioning
confidence: 99%
“…Baffoe-Bonnie (1998) pointed out that the housing market could be "shocked sensitively" by the change of employment and mortgage rates at both national and regional level. Reichert (1990) found that regional house prices reacted to some national economic factors, such as the mortgage rate. Johnes and Hyclak (1999) described how house prices have a great effect on labour force size.…”
Section: Introductionmentioning
confidence: 99%
“…Reichert (1990) studies the influence of local and national economic factors and found that people's income trends, demographic change and employment status are major factors affecting housing prices. Lamont and Steinit (1997) analyzes the relationship between income and housing price using city-level data.…”
Section: Demand Sidementioning
confidence: 99%